Relationship between plasma 25-hydroxymitamin D and leucocyte telomere length by sex and race in a US study. Issue 6 (12th August 2016) - Liu, Jason J.; Cahoon, Elizabeth K.; Linet, Martha S.; Little, Mark P.; Dagnall, Casey L.; Higson, Herbert; Savage, Sharon A.; Freedman, D. Michal
Abstract: A few studies have examined the association between vitamin D and telomere length, and fewer still have examined the relationship in black or male populations. We investigated the cross-sectional association between the vitamin D metabolite 25-hydroxyvitamin D (25(OH)D) concentration in plasma and relative leucocyte telomere length (LTL) in 1154 US radiologic technologists who were 48–93 years old (373 white females, 278 white males, 338 black females, 165 black males). Plasma 25(OH)D concentration was measured by the chemiluminescence immunoassay, and relative LTL was measured by quantitative PCR. Logistic regression was used to obtain OR and 95 % CI for long v . short (based on median) LTL in relation to continuous 25(OH)D, quartiles of 25(OH)D and 25(OH)D deficiency. We found no significant association between continuous 25(OH)D and long LTL in all participants ( P trend =0·440), nor in white females ( P trend =0·845), white males ( P trend =0·636), black females ( P trend =0·967) or black males ( P trend =0·484). Vitamin D deficiency (defined as 25(OH)D<30 nmol/l), however, was significantly associated with short LTL in whites ( P =0·024), but not in other groups. In this population, we found little evidence to support associations between 25(OH)D and long LTL over the entire range of 25(OH)D in the overall study population or by sex and race.